POSSIBILITIES OF APPLYING INDIVIDUAL IFRS PROVISIONS FOR ACCOUNTING DIGITAL ASSETS - Skoryk, Maryna; Kovalchuk, Inna (Український економічний часопис, 2024)
Digital assets are becoming increasingly popular and useful as technological advancements integrate into our personal and professional lives. Data, images, videos, written content, and much more have long been considered digital assets with property rights. Most digital assets, such as a company's brand, can be assigned a value (worth), whether monetary or intangible. Some digital items may only be valuable to the creator or an individual, for example, a family photo on your phone. Others may be valuable to a wider audience. In the past, digital assets, such as data or scanned documents, belonged to organizations and were used to realize their utility. However, when blockchain and cryptocurrency were introduced to the public in 2009, digital assets gained new life and purpose. Everything in digital form became something that could be used to create value in the form of tokenization on the blockchain. The heightened interest in digital assets has led to the need to understand their place among an organization's assets, in developing approaches to formalizing the term "digital assets," options for their assessment, and the methodology of accounting and presentation in financial reporting. The attempt to address the aforementioned issues is the focus of the proposed research.